Associations Between Neonatal Cry Acoustics and Visual Attention During the First Year - Kivinummi, Aicha; Naithani, Gaurav; Tammela, Outi; Virtanen, Tuomas; Kurkela, Enni; Alhainen, Miia; Niehaus, Dana J. H.; Lachman, Anusha; Leppänen, Jukka M.; Peltola, Mikko J. (Frontiers in Psychology, 2020)
It has been suggested that early cry parameters are connected to later cognitive abilities. The present study is the first to investigate whether the acoustic features of infant cry are associated with cognitive development already during the first year, as measured by oculomotor orienting and attention disengagement. Cry sounds for acoustic analyses (fundamental frequency; F0) were recorded in two neonatal cohorts at the age of 0-8 days (Tampere, Finland) or at 6 weeks (Cape Town, South Africa). Eye tracking was used to measure oculomotor orienting to peripheral visual stimuli and attention disengagement from central stimuli at 8 months (Tampere) or at 6 months (Cape Town) of age. Only a marginal positive correlation between fundamental frequency of cry (F0) and visual attention disengagement was observed in the Tampere cohort, but not in the Cape Town cohort. This correlation indicated that infants from the Tampere cohort with a higher neonatal F0 were marginally slower to shift their gaze away from the central stimulus to the peripheral stimulus. No associations between F0 and oculomotor orienting were observed in either cohort. We discuss possible factors influencing the current pattern of results suggesting a lack of replicable associations between neonatal cry and visual attention and suggest directions for future research investigating the potential of early cry analysis in predicting later cognitive development.